Development of thermal management control system of electric vehicle battery charging - Mollik, Md. Sazib (Kulliyyah of Engineering, International Islamic University Malaysia, 2020)
Developing rapid charging protocols for lithium-iron-phosphate (LiFePo4) battery is a key issue for a wider deployment of electric vehicles. A combined experimental and analytical study has been performed to investigate the rapid charging and heat generation characteristics of lithium-iron power battery in the present work. The effect of the internal temperature of the battery has been investigated during the medium, fast, and rapid charge process. The main drawback of LiFePo4 battery is overcharge, overcurrent, extreme condition the separator will melt causing internal short-circuit, the battery will take longer time for charging, and high temperature which affects longevity, efficiency, and battery life cycle. Experimentally investigate the LiFePo4 battery charging characteristics and temperature rise behavior are carried out based on 1C, 2C, and 2.5C charging rate. Moreover, the constant current-constant voltage (CC-CV) charging method has been applied for medium, fast, and rapid charging and analyzing the battery internal temperature using N-type thermistor. Battery charging and thermal management system have been developed based on battery charging performances and levels of raised temperature. Refrigerant-134a cooling system is capable to maintain battery temperature within 20oC~40oC range. Battery charging voltage, current, SOC and battery rasing temperature has been monitor during the charge of LiFePo4 battery. On the other hand, MATLAB/Simulink based custom-designed tool was developed. A dynamic model of lithium-iron-phosphate battery is proposed in this research by considering the significant temperature and capacity fading effects. Results have shown that the LiFePo4 battery can be used for rapid charging up to 85% by maintaining the condition for lifespan of the battery and to shorten the charging time. The simulation results showed that the battery charging model can truly reflect the dynamic output characteristic of lithium-iron batteries. The simulation and experimental results show that the battery can be charged around 1 hour and 55 minutes for medium charging (SOC 100%), 56 minutes for fast charging (SOC 100%) and nearly 31 minutes for rapid charging (SOC 85%). In the experiment, LiFePo4 battery was tested with different charging rates (1C, 2C, and 2.5C). The prototype charger can control battery charging systems for different charging rates such as medium, fast and rapid charging and also able to monitor raised temperature of the battery. Additionally, high charging current has been used for rapid charging where the SOC is 85% due to battery performance. The developed model of a battery charging system shows good performances with several control methods. The LiFePo4 battery operating temperature range is 20oC~40oC where this range has been exceeded for fast, and rapid charging and the experimental battery temperature becomes nearly 47oC. This is why the thermal management system has been developed for fast and rapid charging to control battery temperature. The Variable Frequency Driver (VFD) can control compressor motor frequency where the frequency range is 25Hz-60Hz. Battery average charging temperature has been kept below 25oC, which helps battery performance and lifetime. The evaporator average surface temperature is 14oC which helps for better performance while rapid charging. Experimental results have shown good agreement with simulation results where the maximum variation has been found around 7% only.